Re-experience Japan post Covid-19 pandemic: the impact of Muslim-friendly Japanese street food on Malaysian Muslims tourists behavioral intention / Tengku Sharifeleani Ratul Maknu, Hasman Abdul Manan and Shahira Ariffin - Ratul Maknu, Tengku Sharifeleani; Abdul Manan, Hasman; Ariffin, Shahira (Faculty of Business and Management, 2021)
Several chapters of the Holy Quran have mentioned that tourism is a "Muslim's right." The Quran also revealed that Muslims could visit non-Muslim countries for entertainment, religious, and educational purposes; but has warned its followers to avoid indulging in any behaviors against Islamic law, potentially diluting their faith. Food is a significant component of tourism. However, information about non-Muslim country's local street food effects on Muslim tourists' intention to revisit the destination is somewhat limited. Therefore, this study aims to understand Muslim-friendly Japanese street food's impact on Malaysian Malay Muslims' intention to re-experience Japan post-Covid-19 pandemic via the extended Theory of Planned Behavior. The research may perhaps be part of the early initiatives toward examining Malaysian Malay Muslim tourists' fondness for Muslim-friendly street foods in non-Muslim nations (such as Japan). It may well be an indication of their desire to revisit those countries post the Covid-19 pandemic. Recognizing the variations of food choice behaviors, especially across cultures, denotes a vital information source for relevant agencies in Malaysia and Japan involved in marketing and promoting Japan as a tourist destination post-Covid-19. Japanese street food may well act as the catalyst to revive the tourism economy of both nations.